การสังเคราะห์พอลิเมอร์ลอกแบบโมเลกุลจากพอลิ (3,4-เอทิลีนไดออกซีไทโอฟีน) ผ่านปฏิกิริยาพอลิเมอไรเซชันในสถานะของแข็ง - ปาจรีย์ อ่อนสร้อย (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
3,4-Ethylenedioxythiophene-methanol is one of the interesting monomers for preparation of molecularly imprinted polymers. It is derived from funtionaliation on the 3,4- ethylenedioxythiophene, which opens the opportunity for structural modifications to increase reactivity with template. In this work, using diethyl 3,4-dihydroxythiophene-2,5-dicarboxylate as the precursor passed through nucleophilic substitution reaction. Diethyl 2-(hydroxymethyl)-2,3-dihydrothieno[3,4-b][1,4]dioxine-5,7-dicarboxylate could be synthesized in 24.7%. After that, from hydrolysis reaction and decarboxylation reaction is 2-(hydroxymethyl)-2,3-dihydrothieno[3,4-b][1,4]dioxine-5,7-dicarboxylic acid in 77.7% and 3,4-ethylenedioxythiophene-methanol 38.2% respectively. Molecularly imprinted polymers (MIPs) based on poly(3,4- ethylenedioxythiophene) (PEDOT) were prepared via solid state polymerization (SSP) of 2,5-dibromo-3,4-ethylenedioxythiophene in the presence of 2,4-dinitrophenol as the template molecule. The strong cohesive binding between the synthesized polymer and template molecules prevented the template molecules from being extracted from the polymer by organic solvent. However, the use of sodium hydroxide solution could help extracted off the template molecules. By following the template rebinding experiments monitored by UV-Vis absorption, the conjugated MIPs exhibited the distinctive recognition of the externally added 2,4-dinitrophenol template compared to the non-imprinted polymers (NIPs) prepared in parallel. These accomplishments suggest a possibility to develop the family of PEDOT as highly specific MIP-based sensors.